THE DEPENDENCE OF THE WEAR RESISTANCE OF ELECTRO-SPARK COATINGS IN AN ABRASIVE ENVIRONMENT ON THE STRENGTHENING PHASES - Skvortsov, Oleksandr; Mikosianchyk, Oksana (Problems of Friction and Wear, 2024)
The analysis of the defects of parts of the friction units of aviation equipment under the conditions of abrasive wear was carried out. Types of electrode materials for modification of parts by electrospark alloying are considered. The mechanisms of wear under the influence of free abrasive of electrospark coatings of 1.1645 and 1.3355 steels, HG30 alloy and ZLAB-1 ceramics on structural steels 30HGSA and 45 were analyzed. The dependence of the intensity of wear of electrospark coatings on the hardness of carbides and borides and the ratio of the strengthening phase in the matrix was determined. The low wear resistance of the ceramic coating ZLAB-1 is due to the presence of the boride component ZrB2 of increased microhardness in the matrix phase, which leads to the brittleness of the coating. The predominance of brittle fracture of ESC of 1.1645 steel is caused by the presence of iron carbide up to 16% in the structure of secondary cementite and pearlite of the steel. The increase in wear resistance of ESC made of 1.3355steel is due to the presence of a large amount of W, V and Mo carbides. The phase inhomogeneity of ESC made of HG30 alloy, established by X-ray structural and phase analysis of the coating diffractograms and the activation of oxidation processes during friction lead to an increase in the wear resistance of ESC due to the appearance of W2C tungsten semi-carbide and WC1-x tungsten semi-carbide phases. The obtained results indicate the prospects of ESC made of 1.3355 steel and HG30 alloy with the necessary level of properties to increase the wear resistance of structural steels.